Amplification of human platelet activation by surface pannexin‐1 channels. (June 2014) - Taylor, K. A.; Wright, J. R.; Vial, C.; Evans, R. J.; Mahaut‐Smith, M. P.
Summary Background Pannexin‐1 (Panx1) forms an anion‐selective channel with a permeability up to 1 kDa and represents a non‐lytic, non‐vesicular ATP release pathway in erythrocytes, leukocytes and neurons. Related connexin gap junction proteins have been reported in platelets; however, the expression and function of the pannexins remain unknown. Objective To determine the expression and function of pannexins in human plate‐lets, using molecular, cellular and functional techniques. Methods Panx1 expression in human platelets was det‐ermined using qPCR and antibody‐based techniques. Contributions of Panx1 to agonist‐evoked efflux of cytoplasmic calcein, Ca2+ influx, ATP release and aggregation were assessed in washed platelets under conditions where the P2X1 receptor response was preserved (0.32 U mL−1 apyrase). Thrombus formation in whole blood was assessed in vitro using a shear chamber assay. Two structurally unrelated and widely used Panx1 inhibitors, probenecid and carbenoxolone, were used throughout this study, at concentrations that do not affect connexin channels. Results PANX1, but not PANX2 or PANX3, mRNA was detected in human platelets. Furthermore, Panx1 protein is glycosylated and present on the plasma membrane of platelets, and displays weak physical association with P2X1 receptors. Panx1 inhibition blocked thrombin‐evoked efflux of calcein, and reduced Ca2+ influx, ATP release, platelet aggregation and thrombus formation under arterial shear rates in vitro. The Panx1‐dependent contribution was not additive to that of P2X1 receptors. Conclusions Panx1 is expressed on human platelets and amplifies Ca2+ influx, ATP release and aggregation through the secondary activation of P2X1 receptors. We propose that Panx1 represents a novel target for the management of arterial thrombosis.